2017
DOI: 10.5539/ibr.v10n3p33
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Bankruptcy of Belgian SMEs: A Hybrid Approach Based on Factorial Analysi

Abstract: The aim of this paper is to verify the relevance of technical data analysis which seems to be useful for identifying predictors of bankruptcy of Belgian SMEs. To do so, a sample of 1,860 Belgian companies, including healthy and bankrupt firms, was used. The sample was constituted using Belfirst software (2015). A mixed method data analysis, coupling the Ward aggregation criterion, the method of mobile centres and principal component analysis, was performed on the variables commonly cited in the literature as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 33 publications
2
12
2
Order By: Relevance
“…That is because the ability to obtain a higher corporate profits will affect good financial conditions so that there will be no financial failure at the company. The results of this study are in line with research conducted by Cultrera et al (2017) concluded that there is a negative relationship between profitability and bankruptcy. This ratio measures the amount of profits or profits generated by the company, because the higher the profit earned by the company, the company will be more protected from the risk of bankruptcy.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…That is because the ability to obtain a higher corporate profits will affect good financial conditions so that there will be no financial failure at the company. The results of this study are in line with research conducted by Cultrera et al (2017) concluded that there is a negative relationship between profitability and bankruptcy. This ratio measures the amount of profits or profits generated by the company, because the higher the profit earned by the company, the company will be more protected from the risk of bankruptcy.…”
Section: Resultssupporting
confidence: 91%
“…Because the economic conditions in Indonesia are still uncertain, this results in a high risk of bankruptcy. Potential bankruptcy is a concern for various parties, because bankruptcy is an important matter in stakeholders such as customers, suppliers, investors, creditors, and company employees (Cultrera et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The factor analysis is often used together with other methodologies, in order to improve bankruptcy prediction models (Cultrera et al 2017). Principal Component Analysis (PCA), the statistical procedure that uses an orthogonal transformation to convert a set of observations of possibly correlated variables into a set of values of linearly uncorrelated variables called principal components started to be used in analysis and prediction of bankruptcy risk.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There exist many indicators in financial analysis which allow to assess the risk of bankruptcy of a company (Armeanu et al 2012;Armeanu and Cioaca 2015;Cultrera et al 2017;Arroyave 2018;Prusak 2018).…”
Section: Principal Component Analysismentioning
confidence: 99%